2013
DOI: 10.1073/pnas.1215595110
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of voltage-sensitive fluorescence in a microbial rhodopsin

Abstract: Here, we present a detailed spectroscopic characterization of Archaerhodopsin 3 (Arch). We performed fluorescence spectroscopy on Arch and its photogenerated intermediates in Escherichia coli and in single HEK293 cells under voltage-clamp conditions. These experiments probed the effects of time-dependent illumination and membrane voltage on absorption, fluorescence, membrane current, and membrane capacitance. The fluorescence of Arch arises through a sequential three-photon process. Membrane voltage modulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
189
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(201 citation statements)
references
References 36 publications
12
189
0
Order By: Relevance
“…Because the A225M mutation did not further increase fluorescence in Arch(DETC), we chose to focus on Arch(DETC) for further characterization and engineering. Although an initial mechanistic study of voltage-sensitive fluorescence in Arch was recently reported (18), it remained unclear which amino acid residues should be targeted for mutation to improve fluorescent properties [other than the Schiff-base counter ion, which is known to affect the lifetime of the fluorescence excited state in bacteriorhodopsin (16) and is already mutated in Arch(DETC)]. To identify mutations that increase Arch(DETC) fluorescence, we thus followed an unbiased approach by performing random mutagenesis over the whole protein (details in Materials and Methods) and screened 2,640 mutants in a 96-well plate assay at neutral pH ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the A225M mutation did not further increase fluorescence in Arch(DETC), we chose to focus on Arch(DETC) for further characterization and engineering. Although an initial mechanistic study of voltage-sensitive fluorescence in Arch was recently reported (18), it remained unclear which amino acid residues should be targeted for mutation to improve fluorescent properties [other than the Schiff-base counter ion, which is known to affect the lifetime of the fluorescence excited state in bacteriorhodopsin (16) and is already mutated in Arch(DETC)]. To identify mutations that increase Arch(DETC) fluorescence, we thus followed an unbiased approach by performing random mutagenesis over the whole protein (details in Materials and Methods) and screened 2,640 mutants in a 96-well plate assay at neutral pH ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent spectroscopic analysis suggested that fluorescence of wild-type Arch is low but can be elevated through a sequential three-photon process where two consecutive quanta initialize formation of a highly fluorescent state Q formed from the photocycle intermediate N (18). An alternative approach is utilization of mutations of the Schiff-base counter ion (15) to increase the fluorescence yield in the initial (unphotolyzed) state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…132 Recently, genetically encoded opsins, such as mutants of Arch, have been adapted as voltage sensors. 133 The Arch-derived sensor Arch(D95H) has been shown to have the fluorescence response variations in both amplitude and time course due to voltage change. 134,135 In addition, the Arch variants Arch-EEN and Arch-EEQ have also been demonstrated as voltage sensors with faster kinetics and larger signal intensities compared with Arch(D95H).…”
Section: 131mentioning
confidence: 99%
“…The fluorescence of wild-type Arch-3 appears not to come from the ground state, but from a photogenerated intermediate (see 1 ). Thus a model would need to adopt the correct retinal isomerization state and opsin conformation to reproduce the fluorescence.…”
mentioning
confidence: 99%